Using Sentinel-1 GRD SAR data for volcanic eruptions monitoring: the case-study of Fogo Volcano (Cabo Verde) in 2014/2015 - Tiengo, Rafaela (2022)
3rd Intercontinental Geoinformation Days (IGD), Mersin, Turkey (17-18 november 2021).